Application of block copolymer thin film as a platform for electroless deposition and biosensor - Harandizadeh, Zeinab (Kansas State University, 2020)
This dissertation describes the applications of nanostructured thin films derived from diblock copolymers, polystyrene-block-poly(methylmethacrylate) (PS-b-PMMA) and polystyrene-block-poly(ethylene oxide) with a photocleavable ortho-nitrobenzyl ester (ONB) group (PS-hv-PEO). PS-b-PMMA was used to obtain nanostructured surfaces for testing silver electroless deposition (ELD) with novel sensitization solution, and to prepare gold electrodes coated with nanoporous thin films as platforms for stem-loop probe-based electrochemical DNA (E-DNA) sensors. For the ELD project, thin PS-b-PMMA films on silicon underwent thermal annealing at 190 °C under vacuum condition to induce microphase separation. The thin films were exposed to deep UV for degradation of PMMA and cross-linking of PS, and then washed with acetic acid and water to remove degraded PMMA. The efficiency of silver deposition was compared between nanoscale trenched and ridges obtained on the surfaces of the resulting films. In the E-DNA project, thin films with vertically-oriented nanopores were prepared on gold substrates in the same way as the ELD project except for the temperature for the thermal annealing (170 °C). In the ELD project, our goal was to achieve a spatially controlled deposition of silver nanoparticles on nanostructured surfaces derived from PS-b-PMMA by ELD. We examined stannous acetate (Sn(OAc)₂) (0.5 mM) in dimethyl sulfoxide (DMSO) as a new sensitizer, and compared it with conventional aqueous stannous chloride (SnCl₂) (≥ 5 mM). We hypothesized that Sn²⁺, and thus silver nanoparticles, would be preferentially deposited on nanotrenches formed as a result of the removal of PMMA microdomains due to the higher density of surface -COOH group. However, AFM images revealed that silver nanoparticles were preferentially deposited on nanoridges originating from PS microdomains. The result indicated that silver deposition was controlled by the diffusion of Ag ions toward the surface. Sensitization with Sn(OAc)₂/DMSO was efficient at a low Sn(OAc)₂ concentration due to the reduction of Sn(II) hydroxide formation. In addition, the DMSO solution swelled the polymer, increasing the immobilization of Sn(II) at the polymer film. In the E-DNA sensor project, we used PS-b-PMMA-derived thin films with vertical cylindrical nanopores to investigate the effects of DNA nanoconfinement on the performance of stem-loop probe-based E-DNA sensors. Gold substrates coated with PS-b-PMMA-derived thin nanoporous films (30 nm thick), as well as those without thin films were used as working electrodes. We evaluated the effects of pore size on the sensor performance by using thin films with uniform pore sizes (14, 20, 30 nm). The very thin film (30 nm) permitted counter ions to reach the bottom of the electrode easily, giving a reversible faradaic current in cyclic voltammetry (CV) measurements. The high pore density of these films (570–1220 pores/μm²) let us immobilize a large number of probe DNA molecules on the electrode and thus record a high faradic current. The stem-loop DNA probe was labeled with a terminal methylene blue (MB) redox tag and immobilized onto the gold surface. The faradaic current of the MB decreased by the hybridization of the DNA probe with its target DNA, which was measured at different target concentrations and at different scan rates using CV to assess the hybridization efficiency and the electron transfer rate constant of the MB tag. We observed a current decrease at lower target concentrations for film-coated electrodes as compared with film-free electrodes, indicating the improvement of the limit of detection by electrode coating with a nanoporous film. This result was explained by the manipulated dynamic properties of the MB tag, as suggested by larger changes in its apparent electron transfer rate constant and/or enhanced hybridization within the nanopores. We also assessed the sensor performance in a whole cow blood sample. The sensors with thin film showed smaller interference from redox-active components in whole cow blood, suggesting that the nanopores of the thin film sterically prevented the entry of relatively large interferents. In the third project, we prepared vertically-oriented PEO microdomains in a thin PS-hv-PEO film on a gold substrate via solvent vapor annealing (benzene/H₂O for 3 h). The thin film was irradiated by UV light to photocleave the ONB group and then removed the cleaved PEO in methanol-water solution to obtain a thin film with cylindrical pores (pore diameter: 25 nm) with surface -COOH groups. Apparent -COOH density on the films before amidation was 0.30 ± 0.08 COOH/nm², which was lower than expected, suggesting that the pores did not reach the bottom of the thin film. Subsequently, amidation of the surface -COOH with propargylamine was explored using 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) in 4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid (HEPES) buffer (0.1 M, pH 7). The maximum amidation yield obtained was 58-68%. We tried to increase the reaction yield by trying different amidation methods, but we could not attain the reaction yield higher than 68%. The amidated sample was examined for click reaction with Azide-fluor 545, but the immobilization of the fluorescent dye on the pore surface was unclear.
Keywords: Block copolymer; Thin film; Electroless deposition; Biosensor